2007
DOI: 10.1111/j.1743-6109.2007.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Female Sexual Difficulties and Mental Health in Patients Referred to Two Public and Private Settings in Tehran, Iran

Abstract: Introduction Sexual difficulty has various effects on patients suffering from this condition that can impact on interpersonal and marital relationships. Sexual function may be adversely affected by stress of any kind and emotional disorders. There have been limited studies focusing on the mental health of those suffering from this problem. Aim To determine the relationship between sexual difficulties and mental health in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
(36 reference statements)
5
11
2
1
Order By: Relevance
“…It is also important to remember that psychopathology in the spouse can contribute to sexual maladjustment and ED in male partner due to its effect on the interpersonal relationship domain in general and sexual relationship per se in the form of reduced desire, pain symptoms, reduced satisfaction, reduced pleasure, etc. as reported earlier [30,31]. However, our study did not address this issue.…”
Section: Discussioncontrasting
confidence: 51%
“…It is also important to remember that psychopathology in the spouse can contribute to sexual maladjustment and ED in male partner due to its effect on the interpersonal relationship domain in general and sexual relationship per se in the form of reduced desire, pain symptoms, reduced satisfaction, reduced pleasure, etc. as reported earlier [30,31]. However, our study did not address this issue.…”
Section: Discussioncontrasting
confidence: 51%
“…Azar et al. [52] demonstrated a significant association between depression and sexual difficulties in their study. The rate of sexual dysfunction was reported to be 91.5% among depressed women, whereas it was 66.7% among non‐depressed women.…”
Section: Discussionmentioning
confidence: 67%
“…Their study supported the findings of an earlier study by Dolezal et al [51] in which a link between depression and sexual abstinence was reported. Azar et al [52] demonstrated a significant association between depression and sexual difficulties in their study. The rate of sexual dysfunction was reported to be 91.5% among depressed women, whereas it was 66.7% among non-depressed women.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…En ce sens, les femmes ayant des symptômes dépressifs ont des résultats significativement inférieurs sur plus de la moitié des sous-échelles évaluant le fonctionnement sexuel, i.e., pensées sexuelles et libido (désir sexuel, intérêt sexuel; p < 0,06), fréquence des activités sexuelles, satisfaction sexuelle par rapport au partenaire et problèmes affectant le fonctionnement sexuel (lubrification vaginale, dysfonctions sexuelles, dyspareunie, problèmes affectifs reliés à la sexualité, problèmes orgasmiques, préoccupations sexuelles) et sur l'échelle globale évaluant le fonctionnement sexuel général. Ces résultats concordent avec ceux obtenus dans plusieurs autres études mentionnées précédemment (Azar et al, 2007;Clayton et al, 1997;Cyranowski, Bromberger et al, 2004;Frohlich & Meston, 2002;Kuffel & Heiman, 2006;Mathew & Weinman, 1982).…”
Section: Discussionunclassified